"RABI (Remaja Anti Bertindak Nikah Dini)" Short Film: Based on Local Wisdom to Prevent Child Marriage in Agricultural Areas - Hayati, Nurul; Musviro, Musviro (Journal of Innovation in Educational and Cultural Research, 2026)
Early marriage remains a global concern, hindering the achievement of Sustainable Development Goals (SDGs), particularly gender equality. This practice causes a variety of health problems and violates girls' fundamental human rights, including the right to decide when and whom they will marry. This study evaluates the effectiveness of a short film intervention titled RABI (Remaja Anti Bertindak Nikah Dini), which integrates local wisdom to improve knowledge and attitudes regarding early marriage prevention among adolescent girls in Lumajang, Indonesia. A quantitative approach with a one-group pretest-posttest design was used, involving 137 junior and senior high school students from the Puskesmas Rogotrunan. The intervention consisted of a pre-test, a short film screening, and a post-test. Results revealed a significant improvement in students' post-test scores, with a Wilcoxon test p-value of 0.000, indicating the effectiveness of the intervention. The integration of local wisdom in educational videos enhanced message acceptance and comprehension. The contribution of this research to science is that the results can serve as a reference in health education and efforts to prevent early marriage, thereby improving the knowledge and attitudes of adolescents and contributing to the reduction of early marriages and enhancement of adolescent health. This approach can serve as a relevant medium for adolescent education, requiring further implementation with region-specific adjustments. Collaboration between governments, educational institutions, and communities is crucial to reducing early marriage rates in Indonesia.